2017
DOI: 10.1016/j.arthro.2016.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Can Surgical Trainees Achieve Arthroscopic Competence at the End of Training Programs? A Cross-sectional Study Highlighting the Impact of Working Time Directives

Abstract: The numbers to achieve competent arthroscopic performance in the assessed simulated tasks exceed what is recommended and what is possible during surgical training programs in some countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Specifically, the authors noted that 78 arthroscopic procedures of any kind were necessary to achieve competency in basic diagnostic hip arthroscopy performed on a simulator, whereas more than 610 arthroscopic procedures were necessary to obtain mastery of hip arthroscopy techniques. 10 Similarly, Middleton et al 11 found a threshold of 52 arthroscopic procedures required for competence in basic diagnostic tasks on a shoulder arthroscopy simulator. Furthermore, 248 arthroscopic procedures were required for competence performing a complex task, whereas 476 procedures were required for expertise in complex tasks.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Specifically, the authors noted that 78 arthroscopic procedures of any kind were necessary to achieve competency in basic diagnostic hip arthroscopy performed on a simulator, whereas more than 610 arthroscopic procedures were necessary to obtain mastery of hip arthroscopy techniques. 10 Similarly, Middleton et al 11 found a threshold of 52 arthroscopic procedures required for competence in basic diagnostic tasks on a shoulder arthroscopy simulator. Furthermore, 248 arthroscopic procedures were required for competence performing a complex task, whereas 476 procedures were required for expertise in complex tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, 248 arthroscopic procedures were required for competence performing a complex task, whereas 476 procedures were required for expertise in complex tasks. 11 Price et al 16 demonstrated a significant increase in arthroscopic performance of trainees with increasing experience. The authors discussed that $170 prior arthroscopies were necessary to perform a diagnostic knee arthroscopy at the level of a staff surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the study by Roberts et al 5 is narrow in its conclusion, it does provide the opportunity to stimulate future research that will change how arthroscopic training is taught and evaluated. By combining the methodology of this study with future studies that include global rating scales [6][7][8]…”
mentioning
confidence: 99%